ACBD3 modulates KDEL receptor interaction with PKA for its trafficking via tubulovesicular carrier - Xihua Yue; Yi Qian; Lianhui Zhu; Bopil Gim; Mengjing Bao; Jie Jia; Shuaiyang Jing; Yijing Wang; Chuanting Tan; Francesca Bottanelli; Pascal Ziltener; Sunkyu Choi; et al. (BMC Biology, 2021)
Abstract Background KDEL receptor helps establish cellular equilibrium in the early secretory pathway by recycling leaked ER-chaperones to the ER during secretion of newly synthesized proteins. Studies have also shown that KDEL receptor may function as a signaling protein that orchestrates membrane flux through the secretory pathway. We have recently shown that KDEL receptor is also a cell surface receptor, which undergoes highly complex itinerary between trans-Golgi network and the plasma membranes via clathrin-mediated transport carriers. Ironically, however, it is still largely unknown how KDEL receptor is distributed to the Golgi at steady state, since its initial discovery in late 1980s. Results We used a proximity-based in vivo tagging strategy to further dissect mechanisms of KDEL receptor trafficking. Our new results reveal that ACBD3 may be a key protein that regulates KDEL receptor trafficking via modulation of Arf1-dependent tubule formation. We demonstrate that ACBD3 directly interact with KDEL receptor and form a functionally distinct protein complex in ArfGAPs-independent manner. Depletion of ACBD3 results in re-localization of KDEL receptor to the ER by inducing accelerated retrograde trafficking of KDEL receptor. Importantly, this is caused by specifically altering KDEL receptor interaction with Protein Kinase A and Arf1/ArfGAP1, eventually leading to increased Arf1-GTP-dependent tubular carrier formation at the Golgi. Conclusions These results suggest that ACBD3 may function as a negative regulator of PKA activity on KDEL receptor, thereby restricting its retrograde trafficking in the absence of KDEL ligand binding. Since ACBD3 was originally identified as PAP7, a PBR/PKA-interacting protein at the Golgi/mitochondria, we propose that Golgi-localization of KDEL receptor is likely to be controlled by its interaction with ACBD3/PKA complex at steady state, providing a novel insight for establishment of cellular homeostasis in the early secretory pathway.